2004
DOI: 10.1063/1.1774648
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Inter-Strand Contact Resistance in Epoxy Impregnated Nb3Sn Rutherford Cables

Abstract: An apparatus for the measurement, under transverse pressure, of the inter-strand contact resistance in epoxy-impregnated Nb 3 Sn Rutherford cables has been recently assembled at Fermilab. Procedures have been developed to instrument and measure samples extracted from Nb 3 Sn coils. Samples were extracted from coils fabricated with the Wind-and-React and the React-and-Wind technology, both presently under development at Fermilab. A ceramic binder is used to improve the insulation and to simplify the fabrication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The dependence of the field harmonics on the current ramp rate was very small. The absence of eddy currents in the cable was related to the rather large inter-strand resistance, produced during the cable reaction with synthetic oil without transverse pressure on the cable (Ambrosio et al 2004b).…”
Section: Field Quality Measurementsmentioning
confidence: 99%
“…The dependence of the field harmonics on the current ramp rate was very small. The absence of eddy currents in the cable was related to the rather large inter-strand resistance, produced during the cable reaction with synthetic oil without transverse pressure on the cable (Ambrosio et al 2004b).…”
Section: Field Quality Measurementsmentioning
confidence: 99%
“…It also takes place during quenching and can serve as an indicator of it and possibly as a precursor of it. While the physics of current redistribution is clear and various related processes studied [4[, [5], [12], [32], [33], [34] a significant complication for interpretation in real magnets is the existence of splices (review on splice/joint technology for various superconductors can be found in [35]). Lead splices can be considered in approximation of equal potential for all strands or equal current in all strands with the two giving very different current/power loss distribution outcomes [4].…”
Section: Current Redistributionmentioning
confidence: 99%
“…The experiment proposed relies partially on instrumenting individual strands with voltage taps. This was successfully done at Fermilab in past [32] and the technology is also implemented elsewhere [6], [7], [8]. However, the configuration of the voltage taps requires access to the narrow cable side instrumenting many strands at close proximity.…”
Section: Cable Testsmentioning
confidence: 99%
“…7. Absence of the eddy currents in the cable is related to the quite high inter-strand resistance, created during the cable reaction with synthetic oil without transverse pressure on the cable [8].…”
Section: E Eddy Currentsmentioning
confidence: 99%